2018
DOI: 10.1002/ardp.201800270
|View full text |Cite
|
Sign up to set email alerts
|

Novel quinoline derivatives carrying nitrones/oximes nitric oxide donors: Design, synthesis, antiproliferative and caspase-3 activation activities

Abstract: Novel quinoline derivatives carrying nitrones and oxime as nitric oxide donors were prepared and characterized using different spectroscopic techniques. Nitrones can release nitric oxide in larger amounts compared to corresponding oximes. Antiproliferative screening results showed that the 2-benzylthioquinoline nitrones 6e and 6f and the 2-methylthio analogues 6g and 6h exhibited promising antiproliferative activity especially against leukemia and colon cancer cell lines. Compounds 6c, 6e, and 6f exhibited hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…It inhibits lipid peroxidation by protecting myocardial membranes and inhibiting the membrane peroxidative damage and atherogenesis (Upston, Terentis, & Stocker, ). In the present study, the above nonenzymatic antioxidants such as vitamin C, vitamin E, and GSH were significantly reduced in ISO administered rats and our results are in concord with formerly reported investigations (Abdelbaset et al, ). NRD pretreated rats restored the levels of vitamin C, vitamin E, and GSH in both plasma and heart of ISO rats when compared with ISO alone treated rats.…”
Section: Discussionsupporting
confidence: 92%
“…It inhibits lipid peroxidation by protecting myocardial membranes and inhibiting the membrane peroxidative damage and atherogenesis (Upston, Terentis, & Stocker, ). In the present study, the above nonenzymatic antioxidants such as vitamin C, vitamin E, and GSH were significantly reduced in ISO administered rats and our results are in concord with formerly reported investigations (Abdelbaset et al, ). NRD pretreated rats restored the levels of vitamin C, vitamin E, and GSH in both plasma and heart of ISO rats when compared with ISO alone treated rats.…”
Section: Discussionsupporting
confidence: 92%
“…For more proof of caspase-3 inhibition by our synthesized compounds, cell-based cytochrome C was assayed. It was reported that cytochrome C concentration in the cell has a critical role in the inactivation of caspases and prohibiting the intrinsic apoptosis pathway [ 57 ]. Antiapoptotic proteins can inhibit apoptosis by blocking the release of cytochrome C while proapoptotic members function as activators of its release.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were collected from American Type Culture Collection to be grown in SR containing 10% fetal bovine serum at 37 °C, stimulated with the compounds to be tested for cytochrome C using Cytochrome C Human ELISA Kit (ab119521—Cytochrome C Human ELISA Kit, Vaccera institute, Egypt) [ 57 ] (See Supplementary Materials ).…”
Section: Biochemical Assaymentioning
confidence: 99%
“…Novel quinoline derivatives bearing nitrone or oxime nitric oxide donors are designed. [97] Firstly, all the compounds including starting material, intermediates, and nitrone analogs were investigated for NO releasing ability. Based on results of this activity, quinoline nitrone derivatives were chosen for exploration of antiproliferative effects.…”
Section: Phosphorous Silicon and Sulfur-containing Quinoline Analogsmentioning
confidence: 99%
“…Sulfur and Silicon containing anticancer quinoline molecules B. [95][96][97][98][99] potent MCF-7 inhibitory properties with IC 50 values of 38.…”
Section: Phosphorous Silicon and Sulfur-containing Quinoline Analogsmentioning
confidence: 99%